Measuring the effectiveness of online classes during the Covid-19 pandemic: case study of a government college in Bangladesh - Awal, Rabiul (Journal of Management and Business Education, 2023)
Due to the unprecedented appearance of COVID-19 students throughout the world experienced a significant educational interruption. To minimize the impact of the corona pandemic on educational activities many schools moved their face-to-face classes into online modes during the Covid-19 situation. Although online classes have been introduced instead of face-to-face classes aimed at reducing the educational losses of students, several studies have shown that students feel discomforted and annoyed with the way they learn online and faced several types of challenges. In Bangladesh, many researchers conducted research for exploring the conditions, benefits, and difficulties of online classroom during the COVID-19 pandemic, but all pieces of research were accomplished from the viewpoint of public and private universities in Bangladesh. This study was conducted to explore the effectiveness of online classes during the COVID-19 period from the viewpoint of a government college. The respondents of this study were accounting undergraduate students at Moulvibazar Government Women’s College (MGWC) and data were collected through an online questionnaire survey. This study found that most students recognize online lectures during the corona pandemic as effective and fruitful considering pandemic conditions but in a normal situation, most of the students prefer traditional face-to-face classes over online classes.